Exterior of Pacific Biological Laboratory - Vinnie Lopez:::Photographer::::::::::::; Steven Domingo:::Photographer:::::::::::: (Monterey, California, 2023)
The exterior of Ed Rickett's Pacific Biological Laboratory, 800 Cannery Row in Monterey, CA.